Aktualisasi Konsep Pengukuran Ilmu Fisika Terintegrasi Alqur’an dan As-sunnah - Rachmat Rizaldi; Himsar Himsar (Institut Agama Islam Negeri Padangsidimpuan, 2025)
This research investigates the Qur'anic perspective on physics, specifically focusing on measurement. Employing a qualitative library research methodology, this study integrates an analysis of Qur'anic exegesis. Qur'anic interpretations are utilized to understand the meaning of relevant verses, particularly Surah Al-Qamar (54:49) and Al-Furqan (25:2), and their connection to the concept of measurement in physics. As a library-based study, the primary data sources consist of written materials such as books, journals, tafsir (exegesis) texts, and other documented sources. Secondary data includes Hadith, further interpretive works, physics textbooks, and other pertinent literature. Measurement is defined as the process of comparing a measured quantity with another quantity of a predetermined scale and unit. Measurement has varying applications across different educational levels. In elementary and middle schools, measurement is taught as a topic within science and physics. At the university level, measurement serves as a fundamental course used to prove or test concepts, principles, and facts. The actualization of physics in measurement, based on the Qur'an and Sunnah, can foster attitudes of honesty and carefulness in comparing values in every activity. If measurement is conducted without the guidance of the Qur'an and Sunnah, inconsistencies between theory and fact may arise. Individuals who habitually measure according to Qur'anic and Sunnah concepts will find that their activities and their products align with reality, as dishonesty and negligence are strictly avoided.